DINAMIKA PENGELOLAAN TEKNOLOGI INFORMASI PEMERINTAHAN DAN MODEL CONNECTED GOVERNMENTSEBAGAI SOLUSI - Harimurti, R.M. Agung (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2010)
Various problems continue to hamper the management of government information technology in Indonesia. Among them, are the perception, organization, regulation, governance, and budgeting system. This paper attempts to offer the experience of other countries in the aimplementation of e-governement, as well as introducing the concept of connected government as solutions to overcome problems of information technology management in the government sector.